2013
DOI: 10.1002/tea.21124
|View full text |Cite
|
Sign up to set email alerts
|

Engaging in argument and communicating information: A case study of english language learners and their science teacher in an urban high school

Abstract: This study documents how an urban high school science teacher engaged her English Language Learners (ELLs) in the discourse‐intensive science and engineering practices of (1) arguing from evidence and (2) obtaining, evaluating, and communicating information. The teacher taught an introductory integrated science course to classes with a large percentage (44%) of students who spoke Spanish as their first language. We investigated the instructional strategies this teacher used to support her ELLs in the practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 44 publications
(68 reference statements)
0
32
1
5
Order By: Relevance
“…Many classrooms throughout the world are experiencing shifts in the number of students who speak languages in addition to, or other than, the language of instruction (e.g., Camarota, ). In these classrooms, plurilingual students are positioned to learn science through language competencies that they are still developing (Swanson, Bianchini, & Lee, ). This presents educators with the challenge of constructing learning opportunities that support participation for a range of learners and presents students who are language learners with the challenge of building science understandings while simultaneously building language skills (Lemke, ).…”
Section: Introductionmentioning
confidence: 99%
“…Many classrooms throughout the world are experiencing shifts in the number of students who speak languages in addition to, or other than, the language of instruction (e.g., Camarota, ). In these classrooms, plurilingual students are positioned to learn science through language competencies that they are still developing (Swanson, Bianchini, & Lee, ). This presents educators with the challenge of constructing learning opportunities that support participation for a range of learners and presents students who are language learners with the challenge of building science understandings while simultaneously building language skills (Lemke, ).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, studies have shown how bilingual students' proficiency in the language of instruction result in limited possibilities to learn science (Dutro & Moran, 2003;Honeycutt et al, 2014;Lyon, Bunch, & Shaw, 2012;€ Unsal et al, 2016€ Unsal et al, , 2017. A relevant question to ask then is how to use other resources besides the language of instruction to support bilingual students (Hammond & Gibbons, 2005;Kamberelis & Wehunt, 2012).…”
mentioning
confidence: 99%
“…The author argues that without this, learners’ understanding of key subject‐specific vocabulary, and hence their ability to talk about the subject, may remain underdeveloped. Swanson et al (), however, report that fluent ENSs are nearly three times more likely to participate in whole class conversations than ELLs. Robinson () also suggests that such low participation may be due to limited English vocabulary preventing ELLs from producing active oral contributions.…”
Section: Literature Review and Research Questionsmentioning
confidence: 99%
“…This is despite extensive evidence showing that restricting use of ELLs' native language can hamper learners' understanding of important concepts (Bunyi, 1999;Cleghorn, Merritt, & Abagi, 1989), while its use can help develop learners' subject-specific knowledge (Garcia & Stein, 1997;Ryu, 2015). Awareness among teachers of the potential benefits of using ELLs' native language, however, remains low (Swanson et al, 2014).…”
Section: Science Instruction and Assessment For Ellsmentioning
confidence: 99%
See 1 more Smart Citation